Walter Rauschenbusch: Then and Now - Brackney, William H. (Baptist quarterly, 2017)
Walter Rauschenbusch is one of the great watershed figures in the history of modern Christian thought, ranked in American lore with Jonathan Edwards, Ralph Waldo Emerson, Horace Bushnell, Herman Melville, and William James.1 He has been acclaimed as one of the very few original American theologians, and severely chastised as contributing to the ruination of modern Christian orthodoxy. This article seeks to trace the development of studies about Rauschenbusch's life and thought.